UNLOCKING THE POWER OF BIG DATA: DIGITAL TRANSFORMATION OF PUBLIC POLICY IN DPRD DKI JAKARTA - Ilham Gemiharto (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
This research delves into the prospects and obstacles associated with utilizing large-scale data in developing public policies within the Indonesian context. Integrating big data technology holds promise as a tool for government agencies aiming to refine the public policy formulation process, ultimately providing enhanced services to the populace. Despite its inherent complexity and costliness, incorporating big data offers the government a means to furnish the most up-to-date, precise, and granular information pertinent to developmental issues. For instance, in the agricultural sector, big data can offer an intricate understanding of the diverse requirements of farmers in distinct regions, such as the differentiation between rice varieties sought by farmers in Kalimantan compared to those in Java. Furthermore, the expansive reservoirs of geophysical and meteorological big data hold the capacity to significantly bolster the government's initiatives concerning natural disaster mitigation policies. Nonetheless, the practical integration of big data still needs to be improved by a dearth of comprehensive regulations governing its application. Additionally, the perils of recurrent data breaches in the Indonesian context pose a formidable challenge. This comprehensive analysis concludes that using big data in policy formulation within Indonesia encounters substantial hurdles that threaten to overshadow the potential advantages this technology could offer in enhancing public policy crafting.